Ilmu-ilmu Ushuludin Menjawab Problematika Umat Islam Dewasa Ini - Farid Wajdi Ibrahim (Ar-Raniry: International Journal of Islamic Studies, 2014)
The interpretation of ushuluddin is how the human relationship with God and man to man to avoid inequality, the human beings should be able to put himself as a servant of God ('abd) are always subjecting themselve stoper form the ritual worship. However, as a son human political the human being should also be capable of understanding social phenomena that occurinthe community, andprovide the solutions to the problems that occurin the community in the real life, as well ashow to create the social conditions to be a prosperous society that is blessed by the Almighty.